Detecção da retinopatia diabética no Diabetes Mellitus Tipo 1: comparação entre a oftalmoscopia binocular indireta e a retinografia digital em um estudo populacional. Alterações na espessura da coroide em pacientes com Diabetes Mellitus Tipo 1 sem retinopatia - Malerbi, Fernando Korn [UNIFESP] (2016)
Article 1 Background. Diabetic retinopathy is the main cause of preventable blindness in the economically active population in western countries. Diabetic retinopathy screening is effective in preventing blindness and can be performed through various diagnostic methods. Our objective is to compare binocular indirect ophthalmoscopy (BIO) to telemedicine protocols of digital retinography for diabetic retinopathy screening in a large and heterogenous type 1 diabetes population in a developing country. Methods. Data from 1266 Type 1 Diabetes Mellitus patients from a Brazilian multicenter study were analyzed. Patients underwent BIO and digital retinography, non-mydriatic and mydriatic. Images were sent to a reading center in a telemedicine protocol. Agreement between the different methods was calculated with kappa statistic for diabetic retinopathy and maculopathy classification. Clinical outcome was either observation or referral to specialist. Results. Agreement between BIO and mydriatic retinography was substantial (kappa = 0.67 to 0.74) for diabetic retinopathy observation vs referral classification. Agreement was fair to moderate (kappa = 0.24 to 0.45) between retinography and BIO for maculopathy. Poor mydriasis was the main obstacle to image reading and classification, especially on the nonmydriatic strategy, occurring in 11.9% or right eyes and 16.9% of left eyes. Conclusion. Mydriatic retinography showed a substantial agreement to BIO for diabetic retinopathy observation vs referral classification. A significant amount of information was lost on the non-mydriatic technique because of poor mydriasis. We recommend a telemedicine-based diabetic retinopathy screening strategy with digital mydriatic retinography, preferably with 2 fields (macula- and optic disc-centered), and advise against non-mydriatic retinography in developing countries. Article 2 BACKGROUND/AIMS: To examine tomographic measurements of choroidal thickness in normoalbuminuric and albuminuric Type 1 diabetes mellitus (T1D) patients without diabetic retinopathy. METHODS: Cross-sectional study. Forty T1D patients without diabetic retinopathy were evaluated by spectral domain optical coherence tomography (SD-OCT); twenty-four agematched healthy subjects were evaluated as a control group. Patients with diabetes were classified into 2 groups: 19 patients were albuminuric and 21were normoalbuminuric. Choroidal thickness was measured from the posterior edge of the retinal pigment epithelium to the choroid/sclera junction at 500-?m intervals up to 1000 ?m temporal and nasal to the fovea. RESULTS: Mean choroidal thickness was increased in patients with diabetes. Albuminuric diabetic patients had a thicker subfoveal choroid in comparison to normoalbuminuric diabetic patients (390?m versus 361?m), and subfoveal CT of both groups of diabetic patients was increased in comparison to the control group (323?m). Analysis of variance showed significant differences subfoveally and at the nasal points (p<0.05). CONCLUSIONS: Albuminuric T1D patients without diabetic retinopathy presented a thickened choroid. SD-OCT evaluation of the choroid revealed significant thickness changes even before diabetic retinopathy was present. An altered CT may be a surrogate for the systemic vascular changes that occur in diabetes, and albuminuria should be acknowledged as a confounding factor in the evaluation of choroidal thickness in diabetic patients.